2020
DOI: 10.18046/j.estger.2020.155.3383
|View full text |Cite
|
Sign up to set email alerts
|

Trade, innovation and agglomeration. A case study for Colombia

Abstract: This paper focuses on the relationship between imports, innovation and population agglomeration within regions in Colombia. The main aim is to identify the source of trade that shapes the relationship between innovation and agglomeration, by distinguishing imports ac­cording to levels of technological intensity. This study attempts to bridge two factors that have been studied separately: trade on the one hand; science, technology and innovation activity (STI), on the other. To control for unobserved he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In support of the Innovation System (IS) theory, it has been found that both education and foreign trade are crucial in the development of new knowledge, technology transfer, and knowledge spillovers (Keller, 2010;Lundvall et al, 2009;Srholec, 2011Srholec, , 2015. Recent contributions to the literature have not only shown that the educational institutions in Colombia should be capable of transferring knowledge to the industry (Vélez-Rolón et al, 2020), but also confirmed that imports are positively related with science, technology, and innovation activities (Guevara-Rosero, 2020) Seminal studies on the IS theory were conducted by Lundvall (1985) and Freeman (1982). While Lundvall (1985) analyzed innovation at the microlevel, whereby the user-producer interactions shaped the development of new technologies and products, Freeman (1982), from a macro-perspective, underlines the relation between innovation and international trade, emphasizing the importance of building a technological infrastructure at the national level.…”
Section: Introductionmentioning
confidence: 96%
“…In support of the Innovation System (IS) theory, it has been found that both education and foreign trade are crucial in the development of new knowledge, technology transfer, and knowledge spillovers (Keller, 2010;Lundvall et al, 2009;Srholec, 2011Srholec, , 2015. Recent contributions to the literature have not only shown that the educational institutions in Colombia should be capable of transferring knowledge to the industry (Vélez-Rolón et al, 2020), but also confirmed that imports are positively related with science, technology, and innovation activities (Guevara-Rosero, 2020) Seminal studies on the IS theory were conducted by Lundvall (1985) and Freeman (1982). While Lundvall (1985) analyzed innovation at the microlevel, whereby the user-producer interactions shaped the development of new technologies and products, Freeman (1982), from a macro-perspective, underlines the relation between innovation and international trade, emphasizing the importance of building a technological infrastructure at the national level.…”
Section: Introductionmentioning
confidence: 96%
“…In support of the innovation system (IS) theory, it has been found that both education and foreign trade are crucial in the development of new knowledge, technology transfer, and knowledge spillovers (Keller, 2010;Lundvall et al, 2009;Srholec, 2011Srholec, , 2015. Recent contributions to the literature not only have shown that in Colombia that educational institutions need to have the ability to transfer knowledge to the industry (Vélez-Rolón et al, 2020), but also confirmed that imports have a positive relationship with science, technology, and innovation activities (Guevara-Rosero, 2020) Seminal studies on the (IS) theory were developed by Lundvall (1985) and Freeman (1982). While Lundvall analyzed innovation at the micro-level where the user-producer interactions shaped the development of new technologies and products.…”
Section: Introductionmentioning
confidence: 98%